2014
DOI: 10.1002/adem.201400010
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors of Ferromagnetic Shape Memory Alloy Ni–Mn–Ga Under Incomplete Magneto‐Mechanical Loading–Unloading Cycles

Abstract: In order to investigate the behaviors of ferromagnetic shape memory alloys (FSMAs) under incomplete magneto-mechanical loading-unloading cycles, a single crystal Ni-Mn-Ga specimen is studied with the use of specially designed and manufactured test equipment. Characterization of the specimen is done, and simple experiments are conducted to approve validity of the findings and measurements by the prepared test rig. Stress-strain responses under different constant magnetic fields as well as strainmagnetic field r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…This gives rise to the same response for all the inner loops. These trends are in agreement with the experimental findings reported by Amrollahipour et al (2014) for magneto-mechanical loadings.…”
Section: An Enhanced Model Considering the Effects Of Loading Historysupporting
confidence: 94%
See 2 more Smart Citations
“…This gives rise to the same response for all the inner loops. These trends are in agreement with the experimental findings reported by Amrollahipour et al (2014) for magneto-mechanical loadings.…”
Section: An Enhanced Model Considering the Effects Of Loading Historysupporting
confidence: 94%
“…The amounts of j i at the end of each cycle are shown in Figure 15(b). On the other hand, Amrollahipour et al (2014) experimentally showed that after each interruption, reorientation resumes at the stress level of arrested point when an FSMA is simultaneously subjected to a compressive stress and a perpendicular magnetic field. Since variant reorientation is the reasoning behind the inelastic response under both biaxial compressive and stress-field loadings, it might be concluded that initial j 0 cannot affect the amount of variant 2 volume fraction even in biaxial cases; consequently, its effects must be considered in conditions in which reorientation starts and finishes.…”
Section: An Enhanced Model Considering the Effects Of Loading Historymentioning
confidence: 96%
See 1 more Smart Citation
“…First, it is required to address errors that may be generated during calibration. By inserting μ 0 H y cr into the equation of B3 in Table 1, the calculated blocking stress—the stress value above which no forward reorientation occurs—is considerably lower than its measured value in practice (Amrollahipour et al, 2014). This would cause a significant error in maximum strain induced by magnetic loading.…”
Section: Constitutive Modelingmentioning
confidence: 82%
“…Figure 4 shows an experimental response in a magnetic loading/unloading cycle at the constant perpendicularly applied compression of 1.41 MPa (Amrollahipour et al, 2014), plotted together with Shirani and Kadkhodaei’s (2015) prediction using the mentioned calibration method. By comparing the two results, it is observed that the predictions of the model during forward reorientation in magnetic loading are in a good agreement with the experimental result (Amrollahipour et al, 2014). However, it is observed that the predictions do not match the reported behaviors during reverse reorientation in magnetic unloadings (Amrollahipour et al, 2014).…”
Section: Constitutive Modelingmentioning
confidence: 99%